MOLECULAR AND CELLULAR MECHANISMS OF STEM CELL MAINTENANCE IN PLANT MERISTEMS: A LITERATURE REVIEW - Prasono, Awanda (Universitas Lancang Kuning, 2025)
Plant meristems harbor stem cells that maintain their capacity for self-renewal while generating daughter cells that differentiate into various tissues and organs. This delicate balance between self-renewal and differentiation is governed by complex molecular and cellular mechanisms. This literature review synthesizes recent advances in understanding the regulatory networks controlling stem cell maintenance in plant meristems, focusing on the shoot apical meristem (SAM), root apical meristem (RAM), and cambium. The review examines key signaling pathways, transcriptional networks, epigenetic regulation, hormonal control, and cellular communication mechanisms that coordinate stem cell maintenance. Recent technological advances in single-cell sequencing, live imaging, and computational modeling have revealed unprecedented insights into meristem function. Understanding these mechanisms has important implications for crop improvement, sustainable agriculture, and plant adaptation to changing environments. This comprehensive review integrates findings from over 50 recent studies to provide a current understanding of the molecular and cellular basis of plant stem cell maintenance